The Relationship Between Daily Dietary Intake of Fiber and Short Sleep Duration in the Presence of Di(2-Ethylhexyl) Phthalate: A Population-Based Study - Lin, Jilei; Cheng, Siying; Zhang, Jing; Yuan, Shuhua; Zhang, Lei; Wu, Jinhong; Chen, Jiande; Tang, Mingyu; Zhao, Liebin; Yin, Yong (Frontiers in Nutrition, 2022)
Objective: This study aimed to evaluate the relationship between daily dietary intake of fiber (DDIF) and short sleep duration (SSD) in the presence of di(2-ethylhexyl) phthalate. Methods: Data of 13634 participants in this study were collected from the National Health and Nutrition Examination Survey (NHANES). The sum of urinary mono-2-ethyl-5-carboxypentyl phthalate, mono-(2-ethyl-5-hydroxyhexyl) phthalate, mono-(2-ethyl)-hexyl phthalate, and mono-(2-ethyl-5-oxohexyl) phthalate was used to evaluate the level of di(2-ethylhexyl) phthalate (DEHP) exposure. The ln-transformed urinary creatinine-corrected DEHP [ln(DEHP/UCr)] level was used in the statistical models. DDIF was divided into tertiles (<5.77g/1000kcal, 5.77-9.04g/1000kcal, and >=9.04g/1000kcal). Results: 13634 participants included in this study were classified into two groups according to the sleep duration. The dose response analysis showed that higher ln(DEHP/UCr) was related to higher risk of SSD(<7h and <6h). Participants in the highest vs. the lowest quartile of DEHP were found to be at increased risks of SSD (<7h, <6h, and <5h). The result of risk of SSD (<7h) was (OR 1.57, 95% CI, 1.40-1.76; Ptrend<0.001), of SSD (<6h) was (OR 1.38, 95% CI, 1.18-1.61; Ptrend<0.001) and of SSD (<5h) was (OR 1.45, 95% CI, 1.13-1.86; Ptrend<0.001). DEHP exposure was found to be associated with SSD (<7h) in a sex-specific manner (Pinteraction= 0.033). A significant interaction between ln(DEHP/UCr) and DDIF(tertiles1 vs. tertiles2) (Pinteraction= 0.02) was detected for the SSD(<7h). Conclusion: Our results showed that there was a harmful association between DEHP exposure and SSD (<7h, <6h and <5h). The ameliorative effects of median level of DDIF on SSD(<7h) in the presence of DEHP exposure were observed in this study.